Ask for the Moon, Settle for the Stars: What is a Reasonable Period to Comply with WTO Awards?. Issue 2 (10th March 2017) - MAVROIDIS, PETROS C.; MEAGHER, NIALL; PRUSA, THOMAS J.; YANGUAS, TATIANA
Abstract: The World Trade Organization (WTO) dispute settlement process allows a defending Member a 'reasonable period of time' (RPT) to implement any findings that its contested measures are inconsistent with WTO law. If agreement on this RPT cannot be reached, Article 21.3(c) of the Understanding on Rules and Procedures Governing the Settlement of Disputes (DSU) provides for the possibility of arbitration on the length of the RPT. The DSU provides limited guidelines on the RPT, stating only that it should not normally exceed 15 months. In practice, Arbitrators have developed the standard that the RPT should reflect the shortest possible period under the domestic legal system of the defending Member to make the changes necessary to comply with the WTO rulings. Our research confirms that in practice Arbitrators have determined this period by 'splitting the difference' approximately between the periods suggested by the complaining and defending Member. In addition, the process appears to reward defending Members that request an RPT that exceeds the 15-month guideline in Article 21.3(c).